Comparison of microbial populations and foaming dynamics in conventional versus membrane enhanced biological phosphorous removal systems. (10th May 2016) - Winkler, M. ‐K. H.; Kröber, Eileen; Mohn, William W.; Koch, Frederic; Frigon, Dominic
Abstract: In this study, molecular community analysis and analytical measurements were combined to assess and compare the identity, functionality, structure, and temporal changes of membrane and conventional enhanced biological phosphorous removal systems (which ran stable over 300 days) and to identify the dynamics of the foam forming population. Magnesium was added to the system with the goal to enhance phosphate removal. Both systems behaved similarly with respect to phosphate and nitrogen removal efficiency and had similar community evenness, but they differed in community composition. A principle component analysis indicated that, the community of the membrane system changed permanently whereas the conventional system returned to approximately its initial composition. The relative intensity of DGGE bands were transformed in a numerical matrix and based on this matrix a model was constructed, which predicted some bands as foam forming bands, which were identified as foam‐forming filamentous bacteria by sequencing.